Value-Based Communication Strategies And Tourism Growth: Effectiveness-Vam Model - Erwin, Erwin; Herwan, Herwan (SEAN Institute, 2024)
This study examines the influence of value-based communication strategies on tourism growth in West Bangka Regency using the Effectiveness-VAM model. The global tourism industry has undergone significant changes due to the development of digital technology and shifts in tourist preferences. Although the COVID-19 pandemic had a major impact, the recovery of the tourism sector is considered crucial for economic growth. The main objective of the research is to analyze the influence of communication quality, employee engagement, organizational support, and work coordination on perceived value by tourists and tourist visits, as well as their impact on the local economy of West Bangka. The research uses a quantitative approach with a cross-sectional design. Data was collected through a survey of 400 tourists visiting West Bangka Regency, selected using purposive sampling technique. Data analysis uses Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that all independent variables significantly influence perceived value and tourist visits. Communication quality has the strongest influence. Perceived value is proven to be an important mediator between independent variables and tourist visits. Tourist visits also significantly influence local economic impact. This research contributes by developing an integrated model that links value-based communication strategies with tourist visits and economic impact in the context of developing regional tourism. The research findings provide evidence-based guidance for tourism stakeholders in West Bangka to enhance destination attractiveness and promote local economic growth. Research limitations include a focus on one geographic area and a cross-sectional design. Future research could expand the geographic scope and use longitudinal designs for more comprehensive understanding.